Pemberdayaan Masyarakat Kurang Mampu yang Terdampak Covid-19 di Kelurahan Limau Manis Melalui Introduksi Ayam Kampung Unggul Balitbangtan dan Pelatihan Ransum - Ridho Kurniawan Rusli; Ahadiyah Yuniza; Gita Ciptaan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
This community service program was carried out for the Ganting's farmers, Limau Manis Village, Pauh District, Padang, and West Sumatra. This activity aims to help the economy of the underprivileged community affected by Covid-19 by introducing the Kampung Unggul Balitbangtan (KUB) chicken and training on formulated rations using local feed ingredients. The method of activities carried out to overcome the problem was counselling, training and assistance by the service team in the form of introducing KUB chickens and practising how to prepare KUB chicken rations. A total of 10 heads of families have assisted 10 KUB chicken breeds, preferred provided they already had a chicken cage. After four weeks of farming KUB chicken, monitoring and evaluation were carried out. This activity results from the community's enthusiasm for receiving new information about KUB chickens and being skilled at raising KUB chickens. This community service activity concluded that about 90% of KUB chickens live. However, KUB chickens' ideal body weight performance has not been achieved because the ration is not optimally provided.